Feminist perspectives on Ottoman urban history. - Maksudyan, Nazan (Deutsches Institut für Urbanistik, 2018)
Der Beitrag stellt die neuesten Forschungsergebnisse der Gender- und Stadtforschung für den osmanischen Fall vor. Unter den Bedingungen des sozialen und kulturellen Wandels im 19. Jahrhundert sahen sich osmanische Frauen mit besonderen Chancen und Herausforderungen konfrontiert, städtischen Raum zu produzieren. Dies geschah im Rahmen der neuen Rollen, die Frauen im Bereich der Philanthropie, der Erziehung und Politik ausfüllen konnten, aber auch indem sie die Gender-Geographien osmanischer Städte aktiv veränderten.

This article provides an overview of the literature that approaches Ottoman urban history with a gender perspective. It juxtaposes the valuable insights and contributions of feminist geographers with the available literature on Ottoman urban history in order to argue that the combination of the two has a great potential to enrich the field. In an attempt to reveal, recover and reconsider the roles, positions and actions of women in the midst of altered or redefined economic, social, political and cultural contexts of Ottoman cities, new scholarship highlights how women could reimagine and reconceive the City, actually neither designed for nor controlled by them, and how in time they could create female-controlled public and semi-public spaces. The negotiations, alliances and agency of women in asserting themselves in the public domain need to be reconsidered, given numerous spatial obstacles and resistance to see them as legitimate actors.
Keywords: Stadtgeschichte; Stadtforschung; Sozialwandel; Stadtraum; Öffentlicher Raum; Stadtgeographie; Frau; Öffentlichkeit; Transformation; Modernisierung; Stadtbevölkerung; Kulturwandel; Genderforschung